Impact of Corrosion in Simulated Body Fluid on Fatigue Characteristics of 3D-Printed Polylactic Acid-Coated AM60 Magnesium Alloys - Seyed Ali Ashraf Talesh; Mohammad Azadi (Surfaces, 2024)
In this research, the pure fatigue behaviors of AM60 magnesium alloy with polylactic acid (PLA) coating (PF-AM60-PLA) and the corrosion fatigue behaviors of magnesium alloy with PLA coating (CF-AM60-PLA) were evaluated. Polymer coating was made by fused deposition modeling (FDM) with a 3D printer and attached to standard fatigue test specimens with glue. Then, after 27 days of immersion in the simulated body fluid (SBF), the high-cycle bending fatigue test was performed on samples. Due to corrosion, the weight of the specimens was reduced by an average of 35%. The corrosion rate decreased in the first 7 days and then increased. PF samples with a coating had an average 49% increase in fatigue lifetime. Regarding the CF samples, despite the use of a 10-times stronger solution, the fatigue lifetime of these samples decreased by only 35%. The field-emission scanning electron microscopy (FESEM) results also showed cleavage plates and striations. In addition, the separation of the glue from the coating and Mg was observed. Corrosion products, in addition to microcracks and holes, were seen on the fracture surface of CF specimens, which caused the stress concentration and the crack initiation. Holes caused by the release of gases were also observed in polymer coatings, which were fabricated by 3D printing.